A hospital based eye health survey to see the pattern of eye diseases in Uttarakhand, India - Bharadwaj, Manu; Singh, Lokesh Kumar; Dutt, Bhaskar (International Journal of Research in Medical Sciences, 2017)
Background: The cause of blindness and low vision differs in different countries and communities. The requirements of eye services also vary according to the need of the native population. Studies showing the pattern of ocular morbidity are needed to build better infrastructure of eye care facilities. Methods: This prospective study was conducted in eye department of Government Doon Medical College, Dehradun, Uttarakhand, India between April 2016 to May 2016.the patients were seen in eye OPD by ophthalmologists. Proper anterior and posterior segment evaluation was done and patients were treated accordingly. Data including the registration number, name of the patient, age, sex and diagnosis were recorded in OPD register and analysed. Results: Total 1259 patients were examined. 605 were male and 654 were female. The mean age of male patients was 43 years and for females was 41.33 years. Refractive error (20.97%) was the commonest ocular morbidity in our study followed by cataract (20.02%), follow ups of cataract surgeries and allergic conjunctivitis. Besides refractive errors total 137 (10.88%) patients were presbyopic. Conclusions: This study shows a slightly exceeding number of female patients, which shows that females are equally aware of their health problems. Refractive errors are the most common cause in present study with cataract being second, may be because of higher mean age of the patients presenting to OPD. In present study allergic conjunctivitis was third commonest cause of ocular morbidity in our district may be due to windy weather. The leading causes of ocular morbidity in our study were refractive errors, cataract, allergic conjunctivitis and, presbyopia. The high prevalence of refractive errors and cataracts shows that hospital still requires an improved infrastructure with spectacle provision to the patients.